Editing Modernity. „Atlas of Modernity” exhibition confronted with some trends in contemporary aesthetics - Jóźwiak, Karol (Hybris, 2016)
In this article I examine the notion of “montage” in the contexts of both Muzeum Sztuki exhibition “Atlas of Modernity” and contemporary trends in aesthetics. In the exhibition folder there appears the word “montage” which describes a specific methodology of the exhibition. The way “montage” is being used metaphorically in the discourse of aesthetics is by no means new. Thus I decided to dig into the roots of the usage of this notion, which goes back to the beginning of 20th century when Aby Warburg established a new methodology in the visual studies, Walter Benjamin elaborated on his literary montage, and Sergey Eisenstein contributed to general theory of montage. Nevertheless, the very central figure is contemporary theorist Georges Didi-Huberman and his original reading of the above mentioned thinkers. Thus, using this constellation of names, I try to examine, how the notion deriving from cinematography happened to play such an important role in contemporary aesthetics.